Synthesis and Characterization of Photocatalyst for Conversion of CO2 to Methanol under Visible Light Irradiation - Khan, Maksudur R.; Nor Amalina, Hussain; Cheng, C. K. (2014)
The aim of this study is to understand the mechanism for the production of photocatalyst nano-particles of specific shape and size for CO2 conversion into liquid fuel and to investigate the photocatalyst. Carbon dioxide is one of the primary green house gases causing Earth's global warming effect.